Ultra‐thin 3D Nano‐Devices from Atomic Layer Deposition on Polyimide. (1st April 2014) - Eigenfeld, Nathan T.; Gray, Jason M.; Brown, Joseph J.; Skidmore, George D.; George, Steven M.; Bright, Victor M.
<x xml:space="preserve">Abstract</x> A new nanofabrication process for nano/micro‐devices through the combination of inorganic nanomaterials from atomic layer deposition (ALD) on 3‐dimensional organic polyimide substrates is developed. The first suspended ALD structures with multiple patterned suspended levels on the order of 10 nm are fabricated and results surrounding the mechanical stability of ultra‐thin suspended structures are discussed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>